Effect of Miswak on Oral Health - Karama M. T. Al - Nuaimy (College of Education for Pure Sciences, 2013)
ABSTRACT This clinical investigation was undertaken to compare the use of miswak or tooth brush to assess their ability to control plaque and gingival inflammation. In this clinical trail 60 subjects divided into two groups; each containing 30 persons matched in age and gender, 30 of them were instructed to use miswak while other 30 instructed to use tooth brush twice daily for 3 minutes after breakfast and before the bed time. The plaque and gingival indices were measured according to Silness and Löe for the six teeth at the base line and six months after use miswak in first group and second group. The results of the study revealed that there is a significant reduction at p Key Words: Miswak, Chewing Stick, Oral health. INTRODUCTION Miswak or chewing stick or Siwak